Pediatric Sports Medicine: A Comprehensive Review - Abdullah Akkuş; Hüseyin Aslan; Uğur Saraç; Resul Yilmaz; Sümeyye Dursun; Nefise Betül Ercan; Mehtap Yücel; Ceylani Özkaymakoğlu; Ali Tatlici; Ahmet Osman Kiliç; Abdullah Yazar; Fatih Akin; et al. (Turkish Archives of Pediatrics, 2026)
As participation of children in exercise and organized sports increases worldwide, the health care needs of young athletes differ substantially from those of adults due to age-specific physiological, biomechanical, and psychosocial characteristics related to growth and development. Pediatric Sports Medicine (PSM) is a pediatric-based, multidisciplinary subspecialty that encompasses preparticipation physical evaluation (PPE), exercise prescription, management of sports injuries and overuse syndromes, sport-related concussion, heat-related illnesses, assessment of sudden cardiac event risk, relative energy deficiency in sport (RED-S), planning safe sports participation for children with chronic medical conditions, and safeguarding in sport. In the United States, PSM is formally structured through pediatric-based fellowship training and board certification, whereas Europe lacks a standardized model and relies on heterogeneous approaches integrating pediatrics, sports medicine, and rehabilitation. In Türkiye, sports medicine training remains largely adult-oriented. Given that pediatric subspecialty training is strictly based on prior pediatric specialization and that pediatricians are routinely consulted for comprehensive medical evaluations, the absence of a pediatric-based PSM structure has resulted in notable gaps in pediatric-specific PPE standardization, early sport specialization and load management, RED-S screening, integration of school–club–health care systems, and the health care component of safeguarding policies. This narrative review presents a literature-based synthesis of the conceptual foundations and clinical and public health rationale of PSM, summarizes relevant international guidelines and consensus statements, and proposes a feasible framework for its implementation in Türkiye, where this subspecialty has not yet been established.